A study on north-east monsoon rainfall over India - KHOLE, MEDHA; DE, U. S. (MAUSAM, 2003)
The North-East (NE) monsoon is one of the important components of Indian climate system. The aerial extent of NE monsoon generally extends over south-eastern peninsular India. The following five meteorological sub-divisions of India viz. coastal Andhra Pradesh, Rayalaseema, south interior Karnataka, Kerala and Tamil Nadu receive significant amount of rainfall during the NE monsoon. In the present study, using a long period data series 1875-1997, the variability of NE monsoon rainfall over south-eastern peninsula and whole India, is studied. The association of NE monsoon rainfall with El-Nino and La-Nina years is also analysed. It is observed that, the NE monsoon rainfall, over the south-eastern peninsular India is higher (lower) than normal, during El-Nino (La-Nina) years. Also, the probability of NE monsoon rainfall over this region being excess or normal during El-Nino years is very high, 0.93.